Role of intellectual capital in augmenting the start-up intentions of Indians: An analysis using GEM data - Ahmed Musa Khan; Mohd Yasir Arafat; Mohd Anas Raushan; Mohd Saeem Khan; Amit Kumar Dwivedi; Mohd Mohsin Khan; Imran Saleem (Journal of Global Entrepreneurship Research, 2019)
Purpose: Although the intellectual capital (IC) has already received much attention from the researchers in the field of innovation performance, there is still a paucity in the measuring of the role of IC in venture creation. The present study is an attempt to examine the influence of IC on start-ups. Methodology: In this study, a large data set of 3360 respondents from India provided by the largest entrepreneurship research project GEM has been used. A logistic regression technique has been applied to measure the influence of IC on the entrepreneurial intentions. Findings: It has been found that the components of intellectual capital, i.e., knowledge and skills, entrepreneurial opportunities, and the network, has a positive and significant impact on the entrepreneurial intentions. Contribution: To the best of our knowledge, it is among the initial studies, which have examined the relationship between intellectual capital and entrepreneurial intentions. Only a few studies have already been done in developing countries like India by using a large data set.
Keywords: 650